Light source effects on egg production and performance modeling of kub chickens - Yadi Oktariansyah; Afni Salhsa Billa; Masito Masito (STKIP Persada Khatulistiwa Sintang, 2026)
Lighting intensity strongly influences reproductive physiology and productivity in laying hens. This study examined the effects of different light intensities and lamp types on egg production traits in KUB chickens and modeled production dynamics using nonlinear regression. Four treatments were tested: control, 5-watt blue LED, 5-watt incandescent, and 5-watt white LED. Daily egg count, Hen Day Production (HDP), total egg weight, and average egg weight were analyzed using one-way ANOVA and Tukey’s HSD. Results showed that higher light intensities significantly increased egg count, HDP, and total egg weight (p < 0.05), while average egg weight remained unchanged. Logistic models best fit incandescent and white LED groups, whereas blue LED data aligned with an Exponential model. White LEDs offer an energy-efficient option for improving productivity.